Pengaruh Karakteristik Tugas terhadap Keefektifan Bentuk Pengendalian Akuntansi, Perilaku dan Personal dalam Peningkatan Kinerja Manajer Riset dan Pengembangan - Faisal Faisal; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2013)
The distinctive feature of R & D task, such as lack of routines, may potentially influence the effectiveness forms of control. Perrow’s model of technology and structure (1970) is drawn to explore the influence of task characteristics. This study tests the influence of task characteristics (number of exceptions & task analyzability) on the effectiveness of accounting, behavior and personnel forms of control to managerial performance in research and development setting. Respondents   participating in the study are managers and sub managers in research and development divisions. The study uses survey method. Of the 388 questionares sent, 86 were returned and 57 were used in analysis. The method used in analysis is multiple regression. The result shows that accounting control contributes to organization effectiveness, particularly where task characteristics are low number of exceptions and low task analyzability. By contrast, behavior and personnel controls do not appear compatible where task characteristics are low number of exceptions and low task analyzability. In addition, the result suggests that task characteristics prove to have significant influence on suitability of the control. The result fails to confirm prior study which stated that accounting control was not suitable in research and development setting.